Hubungan Tugas Kesehatan Keluarga Dengan Perilaku Merokok Pada Remaja Di SMA Negeri 1 Maesaan - Angela Natalia Rumondor; Septriani Renteng; Kristamuliana Kristamuliana (JURNAL KEPERAWATAN, 2022)
Background: Smoking behavior is one of the habits that can be carried out by children, adolescents, and adults even though smoking has become a habit. culture. One of the factors that cause smoking behavior in adolescents is family. The family has an important task in maintaining, maintaining and achieving the health of family members, namely the task of family health. Objective: To determine the relationship between family health tasks and smoking behavior in adolescents at SMA Negeri 1 Maesaan. Method: The type of research used by the researcher is quantitative research, with a cross-sectional study approach, namely the measurement of variables is carried out once at the same time. The sample in this study Consisting of 119 male students using Stratified Random Sampling. Results: Family health task recognizes problems Able (94.5%), Unable (5.5%), Deciding on Action Able (99.1%), Unable (0.9%), Providing health care Able (90, 0%), Unable (9.1%), Modifying the environment Able (95.5%), Unable (4.5%), Utilizing health services Able (68.2%), Incapable (31.8% ), Overall family health tasks Able (99.1%), Not able (0.9%), Smoking behavior Smoking (60.9%), Not smoking (39.1%). Conclusion: The research conducted showed that there was no relationship between family health tasks and smoking behavior in SMA Negeri 1 Maesaan.Keywords: Family Health Tasks, Smoking Behavior